An assessment of HDPE fillers and Fiber Wrapping on the strength of Reinforced Concrete (Fracture and Structural Integrity, 2023)
Fiber-reinforced polymer (FRP) is the most promising technique in the present era to bring sustainability, reliability, and pseudo ductility to concrete structures due to its superior properties. Thermoplastic and thermoset polymers are the most thrown-out synthetic waste that contributes to environmental pollution for a long time. Knowing this issue an attempt was made to use High-Density Polyethylene Fiber (HDPE) fillers of size 40x2 mm has been used in concrete. This investigation aims to estimate the integrity effect of HDPE fillers incorporation and wrapping of concrete with Basalt fiber mats (BFM) and Geo-textile fiber mats (GFM) on split tensile strength, shear strength, and impact resistance as per standards. Results indicate that the addition of an optimum quantity of HDPE has a significant effect on improving the tensile, shear, and impact strengths. Adding HDPE fillers in the range of 0.5 - 1.5% in concrete samples wrapped with Basalt and Geo-textile fiber mats showed an increased tensile strength of up to 14.06% and 7.40% respectively with that conventional concrete. Further, wrapping of concrete using Basalt fiber and geotextile fiber mats showed a 4.16% and 20% increase in shear strength for 0.5% HDPE-incorporated concrete samples. Higher impact resistance was also observed for HDPE-added and fiber-wrapped concrete samples.
Keywords: Fiber Reinforced Polymer; Split Tensile Strength; HDPE; , Shear Strength; Impact Resistance